Associations between Serum Ceruloplasmin Level, Obesity and Metabolic and Inflammatory Indexes - Seyyed Morteza Safavi (مجله دانشکده پزشکی اصفهان, 2012)
Background: Among the pathophysiological mechanisms of obesity, obesity-induced inflammation has been suggested as a potential link with obesity-related metabolic disturbances and chronic disease. Recently, some studies have proposed serum ceruloplasmin (CP) level as a risk factor for cardiovascular diseases. In this study, we aimed to investigate the relation between serum CP level (as a new biomarker for obesity) and obesity. Methods: In a case-control study in Isfahan, Iran, 61 obese persons with body mass index (BMI) ≥ 25 kg/m2 (case group) and 61 persons with BMI < 25 kg/m2 (control group) were evaluated. Serum CP level, fasting blood sugar, total cholesterol, low density lipoprotein cholesterol (LDL-c), high density lipoprotein cholesterol (HDL-c), triglyceride, and high sensitivity C-reactive protein (hs-CRP) were measured in all subjects. Findings: There were no significant associations between serum CP level and BMI either among the whole population or in any the case and control groups separately. Correlation analysis showed that serum CP level was positively correlated with serum triglyceride. No significant association was observed between CP and other variables. Conclusion: Serum CP level was not related with obesity in this group of subjects. However, we found a significant positive association between serum CP and triglyceride levels. Keywords: Ceruloplasmin, Obesity, Body mass index, Inflammation